Analisa Semiotik Denotasi, Konotasi dan Mitos Iklan Indomie Versi 45th Anniversary di Televisi - Andriyanto Andriyanto (Jurnal Manajemen Bisnis dan Kewirausahaan, 2022)
This research aims to explain the meaning of denotation, connotation and myth contained in Indomie instant noodle ads version "45th Anniversary". The object of this research is Indomie advertisement version "45th Anniversary" where the advertisement is made for celebrating 45th anniversary of Indomie and coinciding with the independence month of Republic of Indonesia in 2017. Type of this research is descriptive research which has complete picture of a phenomenon or event that is happening as its purpose. This research takes primary data in the form of "45th Anniversary" Indomie advertisement which was taken from television media on one of the television programs, to make this research easier, the researcher downloaded the advertisement at one of internet site that has Youtube.com as its site domain. The study of this research theory comes from several books, previous studies, articles, journals and other sources through internet media which contains Roland Barthes theories about denotation, connotation and myth. This research attempts to analyze the "45th Anniversary" Indomie advertisement by segregating the ads into manageable sections to get an important and learned picture to be shared with others. This research focuses on the tradition of semiotic communication proposed by Craig and particularly by Roland Barthes’ semiotic theory.